Removal of colloidal particles from colloidal waste by use of particle immobilization in gel - Iwata, Masashi; Jami, Mohammed Saedi (2009)
A new method utilizing particle immobilization in gel is proposed for solid-liquid separation of difficult-to-filter colloidal suspensions. A mixture of alginate aqueous solution and colloidal suspension is added to a calcium cWoride aqueous solution, resulting in calcium alginate gels. The gel suspension is drained gravitationally, followed by mechanical expression of the gel particles. During the expression, the colloidal particles remain in the gels and the expressed liquid is clear. Aperture size of gel network can be controlled by addition of sodium carboxymethyl cellulose to the alginate aqueous solution. Car wax emulsion and cyclohexane emulsion are effectively treated by this method. It is possible to extend this method for the removal of dissolved matter, provided that an appropriate colloidal sorbent is selected.